SOCIAL MEDIA UTILIZATION IN DIGITAL JOURNALISTIC PRACTICES: A SURVEY OF AJI MAKASSAR JOURNALISTS - Sri Nabila Safnas; Hartinah Sanusi; Haidir Fitra Siagian (Laboratorium Ilmu Komunikasi Fisip UHO, 2026)
This study examines how journalists affiliated with the Alliance of Independent Journalists (AJI) Makassar integrate social media into their digital newswork through the lens of the Uses and Gratifications (USG) framework. Using a descriptive quantitative survey of 92 journalists, the data were analyzed using descriptive statistics (frequencies and mean scores) and inferential analysis through Spearman correlation to explore the relationship between journalists’ demographic characteristics and patterns of social media use. The findings show that 81.4% of journalists demonstrate high-intensity engagement with social media, indicating its deep integration into routine journalistic practices. Instagram emerges as the dominant platform for both information sourcing (30.4%) and news dissemination (53.3%). Information seeking constitutes the primary motivation for platform use, followed by social interaction, identity expression, and entertainment. Usage intensity is significantly associated with age, professional experience, and media type, with younger and less experienced journalists relying more heavily on social media. These findings highlight the role of social media as a hybrid personal–professional space while reinforcing its function as a platform infrastructure shaping contemporary digital journalism.